PENGARUH KONSENTRASI AGAR BATANG TERHADAP KARAKTERISTIK FISIKOKIMIA DAN ORGANOLEPTIK SELAI LEMBARAN APEL ROME BEAUTY - Sinaga, Gede Tuahta Sisean Marojohan; Suseno, Thomas Indarto Putut; Setijawati, Erni (Jurnal Teknologi Pangan dan Gizi, 2018)
Rome beauty apple jam slice is defined as a modified apple jam into apple jam in a slice form (jam slice) with the main raw materials include apples, sugar, water, citric acid, agar, and HPMC. The advantages of the apple jam slice is more practical because it has the shape and size of the slices that have been adapted to the shape of bread making it easy to prepare. Characteristics of the slice jam is a slice-shaped compact, plastic, and not sticky when removed from the packaging. Production of apple jam slice needs addition of gelling agent (agar and HPMC) to form solid texture. The addition of agar bar can affects Apple jam slice’s characteristics, therefore it is necessary to study the effect of the concentration of agar bar. The methodology of this research is a randomized block design (RBD) with one factor, that is the concentration of agar bar (P), which consists of six levels (0.15% (P1); 0.30% (P2); 0.45% (P3); 0.60% (P4); 0.75% (P5); and 0.90% (P6)) of puree apples used. Repetition of the experiments are carried out four times. Difference concentration of addition agar bar affect moisture content, texture (hardness, adhesiveness, and cohesiveness), and texture organoleptic parameter. Increasing concentration of agar bar caused a decreased of moisture content, syneresis level, and lightness also increased of hardness, adhesiveness, and cohesiveness. Increasing agar bar concentration was not affect taste and color organoleptic. The color of apple jam slice was yellow-red. Best treatment of apple jam slice was addition of 0.60% agar barwhich had moisture content 38.33%, pH 4.36%, hardness 2202.868 g, adhesiveness -1420.147 g.s, cohesiveness 0.143, total dietary fiber 2.58%, also sensory score taste 5.1719, color 4.7526, and texture 5.6518 with score 1-7 as standart.